2023
DOI: 10.7150/ijbs.80351
|View full text |Cite
|
Sign up to set email alerts
|

DBF4 Dependent Kinase Inhibition Suppresses Hepatocellular Carcinoma Progression and Potentiates Anti-Programmed Cell Death-1 Therapy

Abstract: The progression of hepatocellular carcinoma (HCC) remains a huge clinical challenge, and elucidation of the underlying molecular mechanisms is critical to develop effective therapeutic strategy. Dumbbell former 4 (DBF4) complexes with cell division cycle 7 (CDC7) to form DBF4-dependent kinase (DDK), playing instrumental roles in tumor cell survival, whereas its roles in HCC remain elusive. This study revealed that DBF4 expression was upregulated in HCC and constituted an independent prognostic factor of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Further analysis revealed that the following pathways were activated in samples with high DHX37 expression: cell cycle, chemokine signaling pathway, DNA replication, proteasome, primary immunodeficiency, and T cell receptor signaling pathway. Correlation analysis showed that DBF4, STAT1, MCM2, PSMD14, UNG, and CDK4 were core proteins of the above pathways, and correlation analysis indicated that all of them were positively correlated with DHX37 [29][30][31][32][33][34]. We hypothesized that DHX37 may promote HCC progression by interacting with these proteins and thus regulating the related pathways.…”
Section: Discussionmentioning
confidence: 92%
“…Further analysis revealed that the following pathways were activated in samples with high DHX37 expression: cell cycle, chemokine signaling pathway, DNA replication, proteasome, primary immunodeficiency, and T cell receptor signaling pathway. Correlation analysis showed that DBF4, STAT1, MCM2, PSMD14, UNG, and CDK4 were core proteins of the above pathways, and correlation analysis indicated that all of them were positively correlated with DHX37 [29][30][31][32][33][34]. We hypothesized that DHX37 may promote HCC progression by interacting with these proteins and thus regulating the related pathways.…”
Section: Discussionmentioning
confidence: 92%